EFEK SITOTOKSIK DAN PEMACUAN APOPTOSIS FRAKSI PETROLEUM ETER EKSTRAK ETANOL DAUN TAPAK LIMAN (Elephantopus scaber Linn) TERHADAP SEL HELA - Yeni Listyowati; Nurkhasanah Nurkhasanah (Universitas Ahmad Dahlan, 2013)
Elephantopus scaber Linn. has been reported to have cytotoxic effects on breast cancer cells and the potential to be developed as anticancer agent. This study aims was to determine the cytotoxic activity and apoptosis induction effect of petroleum ether fractions of ethanolic extract of (Elephantopus scaber Linn) leaves against cervical cancer cells (HeLa). Petroleum ether fraction was obtained by dissolving eyhanolic extract in petroleum ether, and the soluble fraction was as petroleum ether fraction. The method used for cytotoxic activity test was MTT test. The concentration series used were 2000; 1500; 1000; 800; 400; 200; 100; 50; 25; 12.5; 6.25 and 3.125 mg/ml. The IC50 used as cytotoxic parameters. The apoptotic observations was conducted using acridine orange and ethidium bromide. The study showed the IC50 of petroleum ether fraction of (Elephantopus scaber Linn) ethanolic extract was 185 ug/ml. The study also showed the potency to stimulate apoptosis in HeLa cells.